The relationship of antibodies detected in the Western Blot test with clinical and immunological stages in HIV-infected patients - Korkusuz, Ramazan; Şenoğlu, Sevtap; Işık, Mehmet Emirhan; Işıksaçan, Nilgün; Karaosmanoglu, Hayat; Altuntaş Aydın, Özlem (Journal of Surgery and Medicine, 2022)
Background/Aim: The laboratory diagnosis of human immunodeficiency virus (HIV) infection is based on detection of anti-HIV antibodies in an initial ELISA (enzyme-linked immunosorbent assay) test and its confirmation with the Western Blot (WB) procedure. Even though the specificity of WB is high for the detection of antibodies against various viral proteins, there are important differences in the timing of the appearance of antibody bands and intensities in different stages of HIV infection. The aim of this study was to evaluate antibodies detected in WB testing and the relationship to clinical and immunological stages in HIV-infected patients. Methods: Newly diagnosed 78 patients with HIV/AIDS (Acquired Immunodeficiency Syndrome) in our outpatient department between April 2009 and September 2012 were included in the study as a retrospective cohort. Age, gender, complaints, clinical signs, CD4+ T lymphocyte counts and HIV RNA level at diagnosis were collected retrospectively from medical records. WB band patterns obtained from the reference laboratory of the Istanbul Public Health Center were examined retrospectively. Results: Of the 78 HIV/AIDS cases, 68 (87.2%) were male. Mean age was 38.87(13.09) years (range, 17-83 years). Median CD4+ T lymphocyte count at diagnosis was 410.2 /mm³ (range, 3-1114). Mean HIV RNA level at diagnosis was 592.894 copies/ml. Rare band profiles were seen in 29.4% (23/78). According to World Health Organization (WHO) clinical staging, 59 (75.6%) patients were at stage I, 4 at stage II, 10 at stage III and 5 at stage IV. Gp120, gp160 and gp41, known as envelope glycoproteins in WB band antibodies, were seen in all patients. There was determined to be a decrease in the p17, p51, p55 and p39 bands in WB tests of the advanced grade (Grade IV) of HIV infection. Conclusions: Reduction of p17, p51, p55, p39 antibodies in advanced stages were related with the progression of HIV infection. This shows that WB test is an important parameter not only in the diagnosis of HIV infection, but also in the follow-up of clinical progression in the absence of these antibodies.